Potential of Moringa oleifera Effervescent Granules as a New Antacid: Micronutrients, Formulation, and Evaluation - Mughrbi, Hanin Nafed; Elghnimi, Tamader Youssef; Aljawadi, Jumana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Moringa oleifera, a nutritionally rich plant widely distributed in tropical and subtropical regions, possesses a diverse array of medicinal properties. This study aimed to develop and evaluate effervescent granules from M. oleifera leaves and seeds, assessing their in vitro acid neutralization capacity (ANC) compared to a commercial antacid. Micronutrient content (calcium and magnesium) of both leaf and seed powders was quantified using flame photometry. Effervescent granules were formulated using wet granulation, and their physicochemical properties were evaluated. The ANC was determined in simulated gastric juice. Results revealed that M. oleifera leaves contained significantly higher calcium and magnesium levels than seeds. Two-way ANOVA demonstrated that both leaf and seed effervescent granules, at 5 and 10 g, exhibited significantly higher ANC than the negative control. Post-hoc Tukey's test further indicated that the leaf granules possessed superior ANC compared to seed granules, and equivalent efficacy to 5 g of the commercial antacid. These findings suggest that M. oleifera leaves and seeds can be effectively formulated into effervescent granules with potent antacid properties. The observed ANC, likely attributed to the high micronutrient content of the leaves, highlights a novel nutraceutical application for M. oleifera as a potential alternative to conventional antacids.